Effect of fertilization on the contents of macronutrients and chlorine in tobacco leaves cv. flue-cured (Nicotiana tabacum L.) in two municipalities in Huila, Colombia (2015)
In Colombia, there is little information on tobacco crops and the effect of fertilization on the nutrient content of leaves. The aim of this study was to determine the contents of mineral nutrients in tobacco (Nicotiana tabacum L. cv. flue-cured) plants subjected to different fertilizer rates and sources in two municipalities in the Huila Province (Colombia). Six foliar analyses, with three measurements from vegetative growth to f lowering and three measurements during harvest, were carried out. Seven treatments, including six fertilization alternatives (three doses and two alternative sources of application) and a commercial control, were evaluated. The contents of the macronutrients N, P, K, Ca, Mg, S, and chlorine in the leaves were evaluated. The leaf analyses performed from vegetative growth to f lowering showed differences in the foliar contents of nitrogen, calcium, magnesium, and chlorine between the two municipalities and over time, with contents that increased. During this stage, the elements with higher accumulations in the plants included N, K, and Ca. At harvest, the contents of potassium, magnesium, and calcium decreased over time. For nitrogen, sulfur and chlorine, differences were found in the time-municipality interaction.